Women secondary head teachers in England: where are they now? - Fuller, Kay (Sage, 2017)
The underrepresentation of women in secondary school headship in England and elsewhere is an early and longstanding theme in the women and gender in educational leadership literature. The purpose of this article is to report findings from a statistical survey of secondary school head teachers across England. Data available in the public domain on school websites have been collated during a single academic year to present a new picture of where women lead secondary schools in England. Mapping the distribution of women by local authority continues to show considerable unevenness across the country. This article argues that a geographical perspective still has value. It might influence the mobilization of resources to targeted areas and ultimately result in women’s proportionate representation in school leadership. Alongside this is a need for schools and academy trusts to comply with the Public Sector Equality Duty.